Peningkatan Kapasitas Tim Rujukan dalam Pelayanan Maternal dan Neonatal - Atmaja, Hadi Kusuma; Luthfia, Erien (Jurnal Pengabdian kepada Masyarakat (ABDIKEMAS), 2023)
The health service referral system is one of the efforts to improve the quality of health services which has the impact of reducing maternal and infant mortality due to delays in handling emergencies. The purpose of this community service is as an effort to improve maternal and neonatal referral services. This effort is realized by increasing the capacity of nurses and midwives so that they can provide emergency services quickly and accurately with guaranteed service quality, prioritizing community satisfaction, paying attention to the response time of emergency patients, so that it is expected to reduce neonatal maternal mortality and morbidity. This community service was carried out in East Lombok Regency, West Nusa Tenggara Province in October-November 2022, with the target of a Referral Team consisting of 50 nurses and midwives. The stages of this activity include: preparation, licensing, implementation, and evaluation. The conclusions from the implementation of this community service are: 1) The referral team's understanding of Basic Life Support (BLS) increased to 80% 2) The referral team's understanding of Stabilization and Evacuation of patients increased significantly, which reached 100% 3) All participants had understanding in fluid management 4) After the community service activities were carried out, 100% of the target group had skills in the management of maternal and neonatal referrals. For the continuity of the program, it is suggested that the local regional government and related agencies continue and follow up on this activity, the skills that have been mastered by the referral team should be updated continuously.